China$1 (Bs Road Aheads Problems, Questions, Perspectives - Benedikter, Roland; Nowotny, Verena; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2014)
This book provides a critical commentary on China's situation and future outlook from the perspective of the 2012-13 generational power transfer. In this power transfer, taking place against the background of an increasingly unstable domestic situation, an apparently outstandingly successful generation of (3z(Bhalf-communist(3y (Bleaders, recently increasingly plagued by scandal, transferred responsibility to a generation confronted by mixed expectations and factional in-fighting. Many international observers doubt that the new leadership will have the will or the power to introduce serious reforms in a country that reports 100,000 riots involving more than 500 persons in public areas per year. The China of 2013 seems to be in the midst of a transition seldom seen since the 1970s. The question is if the resulting hope expressed by Chinese dissidents and Western leaders for a (3z(Bnecessary(3y (Bdevelopment of China's still largely autocratic system towards a kind of context-adequate democracy is plausible or not. Featuring incisive commentary by the authors and interviews with experts on the region$1 (Bs political economy, the volume addresses such timely questions as: Should (3z(Brapid democratization(3y (Bof China be the strategic goal of the West or rather a step-by-step approach towards the (3z(Brule of law(3z (Bfirst, and (3z(Billiberal democracy(3y (Bto follow? Should the West be more worried about a thriving China, or a China in crisis? Will China$1 (Bs success contribute to the success of the global community and the world order system, or be a threat to it? What can the West do to help China develop more participatory and inclusive approaches in order to secure social stability? And how can the West strengthen its democratic allies on China$1 (Bs borders? Endorsements (3z(BThis is a book I recommend to students and teachers around the globe. It provides a concise introduction into present China$1 (Bs main problems, questions and perspectives. A must for all who try to understand the rising Pacific giant not through short-term answers, but through long-term questions.(3y (BProfessor Ole Bruun, Institute for Society and Globalization, Roskilde University, Denmark (3z(BThe rise of China to global superpower calls for clear, condensed, yet comprehensive comments for the broader public. This book accomplishes those goals, providing a quick yet comprehensive introduction into what we may expect as the Middle Kingdom seeks to assert what it increasingly sees as its rightful role as a leading world power.(3y (BProfessor Richard Appelbaum, MacArthur Foundation Chair in Global & International Studies and Sociology, University of California at Santa Barbara (3z(BThe new constellation between China and the West needs inspiring departure points of discussion, which may be sober or provocative. This booklet is both in one. It should be used as a basis for in-depth discussion and I recommend it for classrooms and the global civil society debate.(3y (BProfessor Jan Nederveen Pieterse, Mellichamp Professor of Global Studies and Sociology, University of California at Santa Barbaras
Foreword -- Preface -- Chapter 1 Xi Jinping's China -- Chapter 2 The cry for Chinese democratization -- Chapter 3 The 2012-13 generational power transfer and it's perspectives -- Chapter 4 The Ethnonationalism Problem -- Chapter 5 China's new foreign policy and the West -- Chapter 6 China and its neighbors -- Chapter 7 China: The road ahead -- Chapter 8 Perspectives I: Basing China's government on legitimacy and values: An Interview with Peng Bo -- Chapter 9 Perspectives II: Coexistence between Communitarian China and the Individualistic U.S.: An Interview with Robert Martin Less.
Keywords: Economics; Social policy; Economics/Management Science; Emerging Markets/Globalization.; Social Policy; International Relations